Patterns of nucleolar activity during spermatogenesis of two triatomines, Panstrongylus megistus and P-herreri - Tartarotti, E.; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Univ Florence Botany Inst, 1999)
The present work analyzed spermatogenesis in two species of triatomines (genus Panstrongylus) using silver-ion impregnation. The sex chromosomes of P. megistus and P. herreri had nucleolar organizing activity and became strongly impregnated during the phases of meiotic prophase I. Fragmentation of the nucleolus occurred in both species during the meiotic cycle. The nucleolar region could be observed up to diakinesis in meiotic prophase after which only nucleolar bodies and fragments were seen. Postmeiotic reactivation of rRNA synthesis occurred in these two species and was probably related to cell differentiation.
Keywords: nucleolar persistence; nucleolus; Panstrongylus; spermatogenesis; triatomines